CORROSION OF GALVANIZED STEEL AND COPPER IN AQUEOUS ENVIRONMENTS (Journal of Mechanical Engineering, 2014)
Corrosion test of galvanized steel and copper (Cu) has been carried out in three different aqueousenvironments e.g. 5% NaCl solution, sea water and rain water by immersion test technique. Corrosion rate ismeasured in mdd (mg/dm2/day) unit. Corrosion characteristics of the corroded samples are investigated by XRD,XRF and SEM analysis. Irrespective of the exposure duration, Cu is seen better corrosion resistant thangalvanized steel in 5% NaCl solution. Cu corrosion behavior is similar in 5% NaCl solution and the sea wateras well. Formation of protective Cu2O scale on Cu surface is believed to decrease its corrosion rate withincreasing exposure time both in 5% NaCl solution and sea water. Pitting corrosion occurs on Cu surface. Forvery short time exposure Cu is more corrosion resistant but galvanized steel becomes more useful than Cu forlonger exposure in rain water.DOI: http://dx.doi.org/10.3329/jme.v43i2.17828